Educational Stress and Artificial Intelligence Tools: A Study of International Students’ Experiences in Spanish Higher Education - Aida Mehrad; Mohammad Hossein Tahriri Zangeneh; Meriem Bouzedif; Neema George Rweramila (Journal of Asian Social Science Research, 2025)
Stress has become a pervasive challenge for students navigating the demands of modern education, often undermining both academic performance and overall well-being. This study explores the transformative potential of artificial intelligence (AI) tools in alleviating educational stress among international students at C3S Business School in Barcelona, Spain. Employing quantitative methods, the research investigates students’ experiences with AI-powered educational technologies. The findings present a nuanced landscape: many students benefit from the personalized support these tools provide, helping them manage assignments more efficiently and access learning resources with greater ease. For some, this leads to a notable reduction in academic pressure and increased productivity. However, the advantages are not uniform. Several participants voiced concerns about the overreliance on technology, ethical issues, and the risk of diminishing critical thinking skills. The study also highlights the varied ways AI tools are adopted, influenced by demographic factors, individual learning preferences, and academic disciplines. Ethical considerations—particularly around data privacy and academic integrity—emerge as central themes. In conclusion, the research advocates for the thoughtful and ethical integration of AI in education, emphasizing its potential to enhance student engagement and learning outcomes while safeguarding academic values.